Pengaruh Pola Asuh Ibu Balita terhadap Anak Balita di Desa Jombang, Timbulharjo, Sewon, dan Bantul - Pri Hastuti (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The " Toddler Family Class " program provided an opportunity for parents to actively engage in learning about the importance of appropriate parenting for toddlers. Recognizing the critical window of early childhood, the program focused on equipping parents with the knowledge and tools to promote their children’s cognitive, emotional, and social development. Parenting practices in early childhood significantly influence a child’s future academic success, emotional well-being, and ability to form healthy relationships. Therefore, it is essential to ensure that parents are well-informed about the best approaches to child-rearing during these formative years. The interactive discussions offered parents a platform to share their personal experiences, concerns, and challenges regarding parenting. Case studies presented real-life scenarios that allowed participants to apply theoretical knowledge to practical situations. This approach facilitated a deeper understanding of the various parenting styles, including authoritarian, permissive, and democratic parenting, and their respective effects on child behavior and development. Furthermore, the program emphasized the importance of nurturing a secure attachment between parents and toddlers. Participants were introduced to strategies that encourage positive reinforcement, empathy, and effective communication with their children. These strategies are key to fostering a supportive and loving environment in which children can thrive emotionally and socially. The collaborative nature of the program also helped to build a supportive network among parents. They were encouraged to form lasting relationships that could provide ongoing mutual support in their parenting journey. This communal learning environment reinforced the importance of family-centered child development practices, ensuring that parents felt empowered to make informed decisions that would benefit their children’s long-term growth and well-being.